Community Engagement in the Planning Phase of Community Projects Sustainability in Kenya - King’ola Cosmas Mulinge; Damian Boniface Sambuo (Pusbindiklatren Bappenas, 2024)
This study determined the effect of community engagement in the planning phase of community projects sustainability in Kenya. Participatory development theory, positivist philosophy and descriptive research design guided the study with randomly selection of 200 workers who filled the questionnaire. Results from descriptive statistics and inferential analysis, revealed that, community has ample opportunities to provide inputs for planning of project. Community engagement in the planning phase had positive significant influence on project sustainability. The study recommends on implementation of structured mechanisms for community involvement in projects. Engagement strategies throughout the implementation phase and transparency are also recommend to foster effectiveness during monitoring and evaluation of community development projects. The critical role of leadership in facilitating effective community involvement to improve engagement and project sustainability is recommended for future study.